Nephrolithiasis as a common urinary system manifestation of inflammatory bowel diseases; a clinical review and meta-analysis - Mahboube Ganji-Arjenaki; Hamid Nasri; Mahmoud Rafieian-Kopaei (Journal of Nephropathology, 2017)
Context: The extra-intestinal manifestations of inflammatory bowel disease (IBD) are common and involve other organs or systems for example; urinary system. Evidence Acquisitions: For this review, we used a variety of sources by searching through Web of Science, PubMed, EMBASE, Scopus and directory of open access journals (DOAJ). Results: Urinary complications may occur in up to 22% of patients and nephrolithiasis or renal/kidney stones have been suggested to be a common manifestation of disease in forms of uric acid, calcium phosphate or calcium oxalate. We performed a meta-analysis on five clinical trials and reported that correlation between IBD and formation of stone in renal system is positive and significant (Fix-effect model; CI: 95%, P <0.001, and randomeffect model; CI: 95%, P = 0.03). Conclusions: Based on the reports of the clinical trials, calcium oxalate is more prevalent in Crohn’s disease (CD) than in ulcerative colitis (UC).